Emergence of Equine West Nile Encephalitis in Central Macedonia, Greece, 2010. Issue 6 (7th February 2015) - Bouzalas, I. G.; Diakakis, N.; Chaintoutis, S. C.; Brellou, G. D.; Papanastassopoulou, M.; Danis, K.; Vlemmas, I.; Seuberlich, T.; Dovas, C. I.
Summary: During the summer of 2010, an outbreak of West Nile virus (WNV) infections attributed to a lineage 2 WNV strain was reported among humans and horses in Central Macedonia, Northern Greece. Here, the clinical and laboratory investigation of horses that showed severe neurological signs due to WNV infection is being described. Specifically, between August and September 2010, 17 horses with neurological signs were detected. WNV infection was confirmed in all 17 clinical cases by applying laboratory testing. The duration of WNV‐specific IgM antibodies in sera obtained from seven of the clinically affected horses was relatively short (10–60 days; mean 44 days). In the regional unit of Thessaloniki, (i) seroprevalence of WNV and fatality rate in horses were high (33% and 30%, respectively), and (ii) the ratio of neurological manifestations‐to‐infections for this virus strain was high (19%). These observations indicate that the strain responsible for the massive human epidemic of 2010 in Greece was also highly pathogenic for horses. This is the first time that WNV infection has been documented in horses with clinical manifestations in Greece. WNV infection should be included in the differential diagnosis of horses with encephalitis in Greece.